Variation and appropriateness of antipsychotic use in long-term care facilities across Newfoundland and Labrador. (May 2021) - Giovannini-Green, Zachary E. M.; Gamble, John-Michael; Barrett, Brendan; Gao, Zhiwei; Stuckless, Susan; Parfrey, Patrick S.
Objective: The use of antipsychotics to treat seniors in long-term care facilities (LTCFs) has raised concern because of health consequences (i.e., increased risk of falls, stroke, death) in this vulnerable population. This study measured geographic patterns of antipsychotic utilization among seniors living in LTCFs in Newfoundland and Labrador (NL) and assessed potential inappropriateness. Method: We analyzed prescription records among adults 66 years and older with provincial prescription drug coverage admitted to LTCFs in NL between April 1, 2011, and March 31, 2014. Patterns of use were analyzed across the 4 regional health authorities (RHAs) in NL and LTCFs. Logistic, Poisson and linear regression models were used to test variations in prevalence, rate and volume of antipsychotic utilization. To assess potential inappropriateness of antipsychotic use, we analyzed data from Resident Assessment Instrument–Minimum Data Set (RAI-MDS) 2.0 forms from NL LTCFs between January 1, 2016, and December 31, 2018. Pearson chi-squared analysis was performed at the RHA and LTCF levels to determine changes in percentage of total prescriptions or antipsychotic prescriptions without psychosis. Results: Between 2011 and 2014, 2843 seniors were admitted to LTCFs across NL; of these, 1323 residents were prescribed 1 or more antipsychotics. Within the 3-year period, the percentage of antipsychotic use across facilities ranged from 35% to 78%. Using data from 27, 260 RAI-MDS 2.0 assessments between 2016 and 2018, 71% (6995/9851) of antipsychotic prescriptions were potentially inappropriate. Discussion: There is substantial variation across NL regions concerning the utilization of antipsychotics for senior in LTCFs. Facility size and management styles may be reasons for this. Conclusion: With nearly three-quarters of antipsychotic prescriptions shown to be potentially inappropriate, systematic interventions to assess indications for antipsychotic use are warranted. Can Pharm J (Ott) 2021;154:xx-xx.